2009
DOI: 10.3349/ymj.2009.50.3.414
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Fentanyl on Phenylephrine-Induced Contraction of the Rat Aorta

Abstract: PurposeFentanyl was reported to inhibit the α1-adrenoceptor agonist-induced contraction. The goal of this in vitro study was to identify the α1-adrenoceptor subtype primarily involved in the fentanyl-induced attenuation of phenylephrine-induced contraction in isolated endothelium-denuded rat aorta.Materials and MethodsAortic rings were suspended in order to record isometric tension. Concentration-response curves for phenylephrine (10-9 to 10-5 M) were generated in the presence or absence of one of the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This is the first study to provide laboratory evidence that dexmedetomidine attenuates alpha-1 adrenoceptor-mediated phenylephrine-induced contraction via blockade of the alpha-1 adrenoceptor. Previous studies have shown that fentanyl attenuates alpha-1 adrenoceptor-mediated phenylephrine-induced vasoconstriction 16 , 17 . Additionally, dexmedetomidine has been shown to inhibit phenylephrine-induced contraction in the internal mammary and gastroepiploic arteries, suggesting that dexmedetomidine may have an intrinsic affinity for the alpha-1 adrenoceptor 7 , 8 .…”
Section: Discussionmentioning
confidence: 96%
“…This is the first study to provide laboratory evidence that dexmedetomidine attenuates alpha-1 adrenoceptor-mediated phenylephrine-induced contraction via blockade of the alpha-1 adrenoceptor. Previous studies have shown that fentanyl attenuates alpha-1 adrenoceptor-mediated phenylephrine-induced vasoconstriction 16 , 17 . Additionally, dexmedetomidine has been shown to inhibit phenylephrine-induced contraction in the internal mammary and gastroepiploic arteries, suggesting that dexmedetomidine may have an intrinsic affinity for the alpha-1 adrenoceptor 7 , 8 .…”
Section: Discussionmentioning
confidence: 96%
“…Four additional simulations were carried out at clinical concentrations, where the drug molecules were added randomly to the water phase. The concentrations used for propofol and fentanyl were 7.1 55 and 1.0 μM, 56 which corresponds to approximately 36 and 4 molecules, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The anesthetic agent could not be used for this experiment because of the effect on vascular responses during organ bath investigations. [33][34][35] After cervical dislocation, thoracotomy was applied to obtain thoracic aorta. Tissues of rats were quickly removed and put into cold Krebs-Henseleit solution.…”
Section: Aortic Ring Isolations and Vascular Response Studiesmentioning
confidence: 99%